Online Music Retail in India - Singh, Pankaj; Kothavale, Pramod (Indian Journal of Marketing, 2011)
This report focuses on determining the best possible option for price discovery for online music retail. The business model is assumed to be sale of ownership of songs in an encrypted form (DRM) which decreases piracy to some extent. The 150 percent rise in digital music sales from 2007-09 globally suggests that there is a potential market to tap in. It could provide an opportunity for new artists to sell their music online in an easier way. With the advantage of reduced costs, growing internet penetration and hence easy access to music, the digital music retail is bound to hit the Indian markets. The online music retail is already big in the US. The internet penetration in India is increasing and online music retail provides a very good option for upcoming artists to launch albums, as it requires much lesser initial investment as compared to selling it through brick and mortar retail stores. The incremental value to sellers also includes advantages of internet like fan base interaction, ease of dynamic pricing, and creative freedom. The incremental values to buyers are greater availability, variety, upcoming artists catering to niche tastes, unbundled songs etc. However, the biggest issue that the music industry is facing today is piracy. Piracy has been controlled to a certain extent in the US. It was achieved through increasing the expected cost (function of loss when caught and probability of being caught) of downloading pirated music. This was coupled with education on piracy and huge number of options for buying cheap legal music online. Also, music companies in the US used access control technology (like DRM) and provided superior quality music online. However, the weak legal framework in India prevents such protection of intellectual property in India. The customers in India can be segmented into music lovers, enjoyers and casual listeners. The prime prospects are internet users belonging to lovers and enjoyers segments. The reference price for most of the customers in India is nearly 0 as they are used to downloading free music. Few customers compare it to retail price of albums to deduce a reference price of 8 to 10. The possible pricing options are: 1. Bidding: Users can listen to clips of songs and bid their willingness to pay for the song for a pre-announced period before the release. The data from the bids can be used to estimate the latitude of price acceptance. The price can then be set within the LPA depending on the pricing objective. The LPA will be different for each song and thus value for each song can be maximized. However, this model hampers impulse buying, and there will be downward bias and noise in the data, making analysis difficult. 2. Set Price Value based Pricing: Based on primary research, we came to the conclusion that the LPA for songs is from 0 to 5 (min can be based on cost structure). We think this is the best option for the situation in India where users are not yet open to the idea of paying for music online. 3. Based on competitive prices in brick and mortar retail: This option is not feasible as discussed in the analysis.